Recent Metal-Catalyzed Methods for Thioether Synthesis - Geiger, Valentin J.; Oechsner, Regina M.; Gehrtz, Paul H.; Fleischer, Ivana (Synthesis, 2022)
This review summarizes the more recent methods (since 2015) for the synthesis of thioethers using homogeneous metals as catalysts. The thioether moiety can be found in numerous compounds for pharmaceutical, agricultural, or material applications and it is therefore important to develop new, efficient methods for their synthesis. The recent efforts in this field focus on the use of non-precious metal catalysts, as well as on the development of new bond-forming processes.1 Introduction2 Cross-Couplings3 C–H Activation4 Hydrothiolation5 Carbothiolation6 Miscellaneous7 Conclusion
Keywords: thioethers; sulfides; homogeneous catalysis; coupling; hydrothiolation; C–H activation; decarbonylation